Pengembangan Media Bakiak Ular Tangga Untuk Meningkatkan Pemahaman Geometri Dasar Pada Anak Usia 5-6 Tahun - Fathimatuzzohrah Fathimatuzzohrah; Rabihatun Adawiyah; Zuhut Ramdani (Jurnal CARE (Children Advisory Research and Education), 2021)
This study aims to develop learning media of bakiak ular tangga to increase understanding of the basic geometry of children 5-6 ages. The development model of this study used Borg and Gall which consisted of 6 stages. Products developed were validated by a team of experts. The subjects of small scale were 5 children and large scale 25 children. The instrument used to collect the data was observation sheet. The results showed that the results of the validation of the media expert obtained a score of 31 with an average score of 3.8 which categorized "very good", the results of the validation of the material experts obtained a score of 28 with an average score of 4 which categorized "good". The observation results obtained that the percentage value of the pretest success was 40% (MB) and 78% (BSB) posttest and the results of hypothesis testing between the pretest and posttest using the t-test were -20.476 < 2.048. From these results, it can be concluded that the bakiak ular tangga learning media was feasible to use to improve understanding of the basic geometry of children 5-6 ages. Keywords: media, bakiak ular tangga, basic geometry of children 5-6 ages.